2022
DOI: 10.31539/josing.v3i1.4087
|View full text |Cite
|
Sign up to set email alerts
|

Tele-Education in Family and Patients in HIV/AIDS Management During Treatment

Abstract: This study aims to analyze how the influence of vidio learning media on student competency achievement. The method used in this study was carried out by taking data from PubMed, ProQuest, Google Scholar databases, which were found in 2015-2021. The results showed that some of the learning media used by students were Vidio. In conclusion, Vidio as a learning medium is very influential in increasing knowledge, helping to get information about assignments, knowing the development of information, and can be used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…9 A systematic literature review was published in 2022 that analyzed six studies from three databases over five years to assess the tele-education capabilities of mHealth. 10 It focused on patients with HIV/AIDS and their families during treatment. It is concluded that the development of mHealth applications for the treatment and management of HIV can provide rigorous monitoring, research, and evaluation.…”
Section: Introduction Rationalementioning
confidence: 99%
“…9 A systematic literature review was published in 2022 that analyzed six studies from three databases over five years to assess the tele-education capabilities of mHealth. 10 It focused on patients with HIV/AIDS and their families during treatment. It is concluded that the development of mHealth applications for the treatment and management of HIV can provide rigorous monitoring, research, and evaluation.…”
Section: Introduction Rationalementioning
confidence: 99%